Factors Affecting the Prevalence of Fecal Pathogen Infections: Approaches for Health Risk Protection: 10.32526/ennrj/19/2020243 - Koottatep, Thammarat; Taweesan, Achara; Kanabkaew, Thongchai; Polprasert, Chongrak (Environment and Natural Resources Journal, 2021)
Septic tank sludge or fecal sludge (FS) is often discharged on public areas without any treatment, causing environmental and adverse public health effects. Millennium Development Goal 7c (MDG 7c) targets improved access to water and sanitation because 85% of the world’s total FS is often discharged on public areas. Like other countries, Thailand faces fecal slugde management (FSM) problems leading to significant fecal pathogen infections, especially in the north and northeastern regions. This study assessed the effects of unsafely-managed FS on human health risks in two cities, Natan City and Tham Lod City in Thailand, that have relatively high liver fluke and diarrhea infections, and identified the factors relating to FSM practices that affect the prevalence of liver fluke and diarrhea infections due to FS. Specific measures were proposed in delivering integrated FSM solutions and health risk protection toward the Sustainable Development Goal No. 6 (SDG6) targets of safely managed sanitation and hygiene services. Based on data collected from these cities from February to May 2019, factors relating to FSM practices that affect the prevalence of liver fluke and diarrhea infections were identified and analysed using multiple regression analysis. Based on the findings, specific measures in delivering integrated FSM solutions and health risk protection toward the Sustainable Development Goals 6 (SDG 6) are proposed. Because no FS treatment facilities operate in Natan City and Tham Lod City, almost 100% of FS is discharged directly into open drains, resulting in diarrhea and liver fluke infections among local people. The findings identified the factors relating to FSM practices that affect the prevalence of liver fluke and diarrhea infections and proposed specific measures in delivering integrated FSM solutions and health risk protection, such as promoting education programmes, avoiding direct FS discharges into open drains and nearby streams, and providing innovative FSM technologies to eradicate fecal pathogen infections.